The effect of butterfly pea flower (Clitoria ternatea L.) kombucha solution as an antibiofilm agent against Porphyromonas gingivalis - Tamara Yuanita; Naia Naurora Sabilla; Awang Bagus Firmansyah; Devi Eka Juniarti; Setyabudi Goenharto; Eric Priyo Prasetyo; Daniyal Lazuardi Ramadhan (Conservative Dentistry Journal, 2026)
Background: Porphyromonas gingivalis is one of the predominant pathogens found in 28% infected root canal cases. This bacterium is capable of forming biofilms that increase its resistance to antimicrobial agents. Sodium hypochlorite (NaOCl) 2.5% is commonly used as an endodontic irrigant due to its strong antimicrobial activity; however, it can be cytotoxic and cause periapical tissue irritation if extruded beyond the apex. Kombucha contains bioactive compounds such as flavonoids, alkaloids, tannins, saponins, and terpenoids, as well as organic acids from fermentation that may inhibit microbial growth. This study investigated the antibiofilm potential of butterfly pea kombucha against P .gingivalis. Purpose: This study aimed to evaluate the effectiveness of butterfly pea kombucha in inhibiting and eradicating P . gingivalis biofilm through the determination of MBIC₉₀ and MBEC₉₉ values. Methods: This laboratory experimental study used a post-test only control group design with nine groups: kombucha concentrations of 100–70%, positive control (NaOCl 2.5%), and negative control. Biofilm inhibition was assessed by the microtiter plate assay with crystal violet staining and optical density reading at 540 nm. Data were analyzed using One-way ANOVA and Tukey HSD (p<0.05). Results: The results showed that MBIC₉₀ was achieved at the 100% concentration, demonstrating biofilm inhibitory activity comparable to the positive control based on the Tukey HSD test (p > 0.05). Conclusion: These findings indicate that high concentration butterfly pea kombucha has potential as a natural antibiofilm agent against Porphyromonas gingivalis.